Let’s Graduate - Omar Qaneer; Jamal SaadEddin (My University, 2024)
"Let's Graduate" is an innovative digital platform tailored for the Faculty of Engineering, designed to enhance the graduation project registration process. This advanced system, accessible through both a website and a mobile application, is specifically crafted to meet the unique needs of the faculty. It focuses on simplifying the registration, supervision, and approval phases for student projects, offering a seamless and user-friendly experience. Central to the system's functionality are its specialized roles and capabilities. Department Managers, serving as administrative users, are responsible for setting and managing graduation project registration requirements within their departments. Students benefit from an intuitive interface that allows for effortless project registration and the ability to connect with supervisors. The system also supports the formation of student partnerships, fostering a collaborative academic environment. "Let's Graduate" also brings robust oversight and evaluative features. Department Managers have tools to oversee and regulate registration activities, ensuring adherence to academic standards. The platform enables students to submit their project abstracts, which are then reviewed and critiqued by supervisors. A dedicated committee evaluates and either approves or rejects these abstracts, maintaining a high standard for project quality. This system not only streamlines administrative processes but also enriches the educational journey for students and faculty, driving forward a culture of transparency, efficiency, and academic excellence.